Screening of Dogs for Leptospira using Sandwich Dot Elisa - Rahul S Nair (Department of VeterinaryEpidemology & Preventive Medicine College of Veterinary and Animal Science, 2004)
An investigation was carried out in 210 dogs of Thrissur district to assess the prevalence of leptospirosis using diagnostic techniques like darkfield microscopy, Sandwich dot ELISA for Leptospira antigen detection, Sandwich plate ELISA for Leptospira antigen detection and Polymerase chain reaction. Sera and urine samples were collected from dogs brought to University Veterinary Hospitals, Kokkalai and Mannuthy that included 109 diseased animals and 101 healthy dogs. Out of the 210 sera samples tested 26 (12.38 per cent) samples, 6 (5.94 per cent) out of the 101 samples from healthy dogs and 20 (18.35 per cent) out of the 109 serum samples from diseased dogs were found positive. Out of the 210 urine samples tested 22 samples (10.48 per cent), eight (7.34 per cent) from diseased dogs and 14 (13.86 per cent) from healthy dogs were found positive for pathogenic leptospires. Prevalence of leptospirosis was found higher in male dogs and in dogs aged from six months to three years. The present finding of healthy carriers for leptospirosis among dogs shows the need of checking dogs more carefully for inapparent leptospirosis because of the human health hazard. Evaluation of the comparative efficacy of the four diagnostic tests revealed darkfield microscopy inferior in detecting leptospires in dogs and the newly developed, easy to perform and cost effective sandwich dot and plate ELISA for Leptospira antigen detection that was showing hundred percent agreements with polymerase chain reaction can be adopted as an effective diagnostic tool for canine leptospirosis even at field level where sophisticated infrastructure is lacking.